2011
DOI: 10.1089/bsp.2011.0031
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Regional Recovery Framework

Abstract: A biological attack would present an unprecedented challenge for local, state, and federal agencies, the military, the private sector, and individuals on many fronts, ranging from vaccination and treatment to prioritization of cleanup actions to waste disposal. To prepare for recovery from this type of incident, the Seattle Urban Area Security Initiative (UASI) partners collaborated with military and federal agencies to develop a regional recovery framework. The goal was to identify key information that will a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As discussed above, the duration of evacuation in this second case is assumed to be six months for the base case. The approach taken here is generally in line with the framework suggested by Lesperance et al . and the results of the Seattle Urban Area Security Initiative (UASI).…”
Section: Methodsmentioning
confidence: 75%
“…As discussed above, the duration of evacuation in this second case is assumed to be six months for the base case. The approach taken here is generally in line with the framework suggested by Lesperance et al . and the results of the Seattle Urban Area Security Initiative (UASI).…”
Section: Methodsmentioning
confidence: 75%
“…While benefiting from the extant natural disaster literature, the model also recognizes that infectious diseases are biological hazards, and therefore, outbreaks present recovery challenges and opportunities distinct from events involving geological or meteorological hazards—for example, decontamination efforts to remove and/or render pathogens nonviable [ 30 ]; enhanced MCM research, development, and production to prevent and treat future infection [ 23 ]; heightened vulnerability of the health sector to outbreak impacts [ 12 , 13 ]; potential secondary chronic health conditions and their socioeconomic effects that require longer-term support and intervention [ 11 ]; primary prevention and mitigation in the form of fewer risky practices at the human-animal-environment interface that lead to pathogen emergence [ 7 ]; and heightened biosecurity and biosafety measures to offset the risk of accidental or deliberate release of a dangerous pathogen [ 3 ].…”
Section: Modeling Postepidemic Recoverymentioning
confidence: 99%
“…16,17 Formal and informal infrastructure, as well as activities and accomplishments, in preparedness-related regional collaboration have been preliminarily explored in a small number of case studies. [18][19][20] A comparative look across case studies found regionalization to be preceded by a variety and combination of impetuses, including enhancing local public health capacity, a perceived need for a coordinated response, or to more efficiently coordinate federal preparedness funding.…”
mentioning
confidence: 99%